The male of Mesoveloidea williamsi Hungerford, 1929 revisited - Moreira, Felipe Ferraz Figueiredo; Ribeiro, José Ricardo Inacio; Nessimian, Jorge Luiz (Zootaxa, 2008)
The present authors recently published in Zootaxa (Moreira et al. 2006) a description of the male of Mesoveloidea williamsi Hungerford, 1929 and new records for southeastern Brazil. The records therein presented are still valid; however, we overlooked the description of the male form published by Jaczewski (1931). Therefore, Moreira et al. (2006) actually presented a redescription of the male of Mesoveloidea williamsi.